Stereotactic Navigation Improves Outcomes of Orbital Decompression Surgery for Thyroid Associated Orbitopathy. Issue 6 (November 2020) - Heisel, Curtis J.; Tuohy, Megan M.; Riddering, Alixandra L.; Sha, Cuilee; Kahana, Alon
Abstract : Purpose: To test whether intraoperative stereotactic navigation during orbital decompression surgery resulted in quantifiable surgical benefit. Methods: This retrospective cohort study examined all consecutive patients who underwent primary orbital decompression surgery for thyroid associated orbitopathy performed by a single surgeon (A.K.) during the periods of 2012–2014 (non-navigated), and 2017–2018 (navigated). The study was HIPAA-compliant, was approved by the Institutional Review Board, and adhered to the tenets of the Helsinki declaration. Recorded parameters included patient age, sex, race, decompression technique (side of operation and walls decompressed), estimated blood loss (EBL), intraoperative complications, times that patient entered and exited the operating room (OR), times of surgical incision and dressing completion, pre- and postoperative best corrected visual acuity (BCVA), proptosis, diplopia, postoperative change in strabismus deviation, and need for subsequent strabismus surgery. Recorded times were used to calculate operating time (initial incision to dressing) and maintenance time (time between OR entry and initial incision and time between dressings and OR exit). The total maintenance time was averaged over total number of operations. Student t test was used to compare surgical times, maintenance times, EBL, and proptosis reduction. Fisher exact test was used to compare BCVA change, strabismus deviation change, resolution or onset of diplopia, and need for corrective strabismus surgery. Results: Twenty-two patients underwent primary orbital decompression surgery without navigation, and 23 patients underwent navigation-guided primary orbital decompression surgery. There were no intraoperative complications in either group. The average operative time was shorter in the navigated group for a unilateral balanced decompression (n = 10 vs. 19; 125.8 ± 13.6 vs. 141.3 ± 19.4 min; p -value = 0.019), and a unilateral lateral wall only decompression (n = 13 vs. 3; 80.5 ± 12.8 vs. 93.0 ± 6.1 min; p -value = 0.041). The average maintenance time per surgery was not significantly different between the non-navigated group (51.3 ± 12.7 min) and the navigated group (50.5 ± 6.4 min). There was no significant difference between the navigated and non-navigated groups in average EBL per surgery. There was no significant difference in BCVA change. Average proptosis reduction was larger in the navigated group, but this was not significant. There was a significantly lower proportion of patients who required corrective strabismus surgery following decompression in the navigated group than in the non-navigated group (39.1% vs. 77.3%, p -value = 0.012). Conclusions: Intraoperative stereotactic navigation during orbital decompression surgery has the potential to provide the surgeon with superior spatial awareness to improve patient outcomes. This study found that use of intraoperative navigation reduced operative time (even without factoring in a resident teaching component) while also reducing the need for subsequent strabismus surgery. This study is limited by its size but illustrates that use of intraoperative navigation guidance has substantive benefits in orbital decompression surgery. Abstract : Use of stereotactic navigation led to improved outcomes in proptosis reduction and strabismus surgery avoidance, while reducing operative time.